A Cluster of Nucleotide‐Binding Site–Leucine‐Rich Repeat Genes Resides in a Barley Powdery Mildew Resistance Quantitative Trait Loci on 7HL. Issue 2 (1st July 2016) - Cantalapiedra, Carlos P.; Contreras‐Moreira, Bruno; Silvar, Cristina; Perovic, Dragan; Ordon, Frank; Gracia, María Pilar; Igartua, Ernesto; Casas, Ana M.
Abstract : Powdery mildew causes severe yield losses in barley production worldwide. Although many resistance genes have been described, only a few have already been cloned. A strong QTL (quantitative trait locus) conferring resistance to a wide array of powdery mildew isolates was identified in a Spanish barley landrace on the long arm of chromosome 7H. Previous studies narrowed down the QTL position, but were unable to identify candidate genes or physically locate the resistance. In this study, the exome of three recombinant lines from a high‐resolution mapping population was sequenced and analyzed, narrowing the position of the resistance down to a single physical contig. Closer inspection of the region revealed a cluster of closely related NBS‐LRR (nucleotide‐binding site–leucine‐rich repeat containing protein) genes. Large differences were found between the resistant lines and the reference genome of cultivar Morex, in the form of PAV (presence‐absence variation) in the composition of the NBS‐LRR cluster. Finally, a template‐guided assembly was performed and subsequent expression analysis revealed that one of the new assembled candidate genes is transcribed. In summary, the results suggest that NBS‐LRR genes, absent from the reference and the susceptible genotypes, could be functional and responsible for the powdery mildew resistance. The procedure followed is an example of the use of NGS (next‐generation sequencing) tools to tackle the challenges of gene cloning when the target gene is absent from the reference genome.